Epitope screening and self-assembled nanovaccine molecule design of PDCoV-S protein based on immunoinformatics - Chen, Yaping; Song, Xinqi; Chen, Wenshuang; Zhao, Xinyi; Yang, Li; Liu, Dongyu (Frontiers in Microbiology, 2024)
Based on the whole virus or spike protein of pigs δ Coronavirus (PDCoV) as an immunogen may have unrelated antigenic epitope interference. Therefore, it is essential for screening and identifying advantageous protective antigen epitopes. In addition, immunoinformatic tools are described as an important aid in determining protective antigenic epitopes. In this study, the primary, secondary and tertiary structures of vaccine were measured using ExPASy, PSIPRED 4.0 and trRosetta servers.Meanwhile, the molecular docking analysis and vector of candidate nano-vaccine were constructed.The immune response of candidate vaccine was simulated and predicted using C-ImmSim server.This experiment screened B cell epitopes with strong immunogenicity and high conservation, CTL epitopes and Th epitopes with IFN-γ and IL-4 positive of Spike protein. Ferritin is used as a selfassembled nanoparticle element for designing candidate nano-vaccine. After analysis, it has been found to be soluble, stable, non-allergenic and has a high affinity for its target receptor TLR-3. The preliminary simulation analysis results show that the candidate nano-vaccine has the ability to induce humoral and cellular immune response. Therefore, it may provide a new theoretical basis for research on coronavirus self-assembled nano-vaccines. It may be an effective candidate vaccine for controlling and preventing PDCoV.